Nullity of marriage: Canons 1620; 1628 (Roman Replies and CLSA Advisory Opinions 2008, 2008)
"This case is interesting because of the number of procedural issues it raises: a negative decision in First Instance; an appeal against that decision and a complaint of nullity against that decision; an interlocutory sentence by the Second Instance court, and an appeal against that decision by Respondent's First Instance advocate. At several points the Rota underscores procedural issues that the case raises, and the two questions to be decided by decree: the nullity of the Appeal Court's interlocutory sentence and whether or not to recommend the case to the Rota. I am grateful to Msgr. Fred Easton for translating the case, and the ponens who made it available. I have made all identifying specifics anonymous."